"Fibula plus Ilizarov": a Simpler Strategy Than Bone Transport for Major Bone Defects in Children. Issue 1 (17th March 2021) - Subramanyam, Koushik N.; Mundargi, Abhishek V.; Umerjikar, Sagar
Abstract : Bone infection in children can cause extensive diaphyseal defects that are challenging to reconstruct. We report a modified technique of ours in 2 of our patients. One was a 10-year-old boy with 8 cm tibial defect and the other was 13-year-old boy with 7 cm femoral defect. The first stage of treatment involved radical debridement, sequestrectomy, antibiotic spacer application, stabilization with conventional external fixation, and 6 weeks of antibiotic therapy. The second stage of treatment consisted of intramedullary autologous fibular strut grafting stabilized with intramedullary K-wire supplemented with corticocancellous graft and stabilized with simple Ilizarov fixator. Patients began full weight bearing walking with fixator at three months of application. Fibular graft incorporated at 4 and 8 months for the femoral and tibial defects respectively. At follow-up of 3 years both patients are independent ambulators with preserved joint range of motion. We present this simple, cost-effective, and replicable technique.